What happens when the price of a tobacco retailer licence increases?. Issue 2 (19th June 2013) - Bowden, Jacqueline A; Dono, Joanne; John, David L; Miller, Caroline L
Abstract : Objective: To measure the impact of a 15-fold licence fee increase on tobacco retailer licence renewals. Methods: The regulatory change increasing tobacco licence fees (from $A12.90 to $A200 per annum) took effect on 1 January 2007. Government Tobacco Licence records (n=7093) were audited for 1 year prior to, and 2 years after the change. An interrupted time series analysis using ARIMA modelling was conducted to examine the impact of fee increases on the number of active licences. Results: The total number of tobacco licences decreased by 23.7% from December 2007 to December 2009. The increased tobacco licence fee implemented on 1 January 2007, was associated with a significant reduction in the number of tobacco licences purchased or renewed in subsequent years. Of the 1144 entertainment licensees holding valid licences in December 2007, 30.9% no longer held a licence by December 2009, and 19.9% had reduced the number of points of sale within the same venue. Conclusions: Licensing of tobacco retailers has received little attention in tobacco control in Australia and internationally. Our data add to the growing body of evidence supporting further regulation of retail sale of tobacco. The results demonstrate that a tobacco licence price increase off a low base is a potentially effective method of reducing tobacco points of sale when consumer demand for cigarette products is low. However, further research is needed to identify additional measures that may be necessary to reduce the availability of tobacco products in areas where consumer demand for cigarettes is high.